Detection of Localized Hepatocellular Amino Acid Kinetics by using Mass Spectrometry Imaging of Stable Isotopes. (11th May 2017) - Arts, Martijn; Soons, Zita; Ellis, Shane R.; Pierzchalski, Keely A.; Balluff, Benjamin; Eijkel, Gert B.; Dubois, Ludwig J.; Lieuwes, Natasja G.; Agten, Stijn M.; Hackeng, Tilman M.; van Loon, Luc J. C.; Heeren, Ron M. A.; et al.
Abstract: Mass spectrometry imaging (MSI) simultaneously detects and identifies the spatial distribution of numerous molecules throughout tissues. Currently, MSI is limited to providing a static and ex vivo snapshot of highly dynamic systems in which molecules are constantly synthesized and consumed. Herein, we demonstrate an innovative MSI methodology to study dynamic molecular changes of amino acids within biological tissues by measuring the dilution and conversion of stable isotopes in a mouse model. We evaluate the method specifically on hepatocellular metabolism of the essential amino acidl ‐phenylalanine, associated with liver diseases. Crucially, the method reveals the localized dynamics ofl ‐phenylalanine metabolism, including its in vivo hydroxylation tol ‐tyrosine and co‐localization with other liver metabolites in a time course of samples from different animals. This method thus enables the dynamics of localized biochemical synthesis to be studied directly from biological tissues.